The privatization and commercialization process of Argentinian universities: its causes and continuities (Praxis Educativa, 2025)
Based on an analysis of what happened in higher education and in the scientific system of Argentina, in this article we will ask the question of whether the extreme right or neoliberal governments of recent decades were the only ones responsible for its commercialization process or whether there were various concurrent causes. We will show that the privatization policy has its origin in big capital and international financial organizations, which were supported by local right-wing or neoliberal governments, and that, on the other hand, the progressive regimes that alternated in power, although they denounced this trend and declared their intention to mitigate it, they were unable to take significant measures to reverse it. We will also raise the probability that a similar phenomenon has occurred in other Latin American countries.
Keywords: universities; privatizations; educational commodification; progressive governments; Argentina